Pengaruh Pengalaman Komunitas terhadap Komitmen Komunitas Merek pada komunitas Sampoerna Retail Community Medan 2 - Nasution, Ahmad Syarif; hermawan, Indra; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina Fawzea (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to explore the relationship between community experience and brand community commitment within the context of offline brand communities. Employing a quantitative approach with a survey method, the study investigates the mediating effect of community experience on brand community commitment. The sample using 80 members of the Sampoerna Retail Community in Area Medan 2, Preliminary analysis indicates a moderate positive correlation between community experience and brand community commitment, with community experience explaining approximately 57.9% of the variability in brand community commitment. This research provides valuable insights into the relationship between community experience and brand community commitment in offline settings. The findings have implications for businesses aiming to strengthen brand community commitment and foster brand loyalty within offline brand communities.